KOMPOSISI VEGETASI PADA HUTAN EBONI DI KELOMPOK HUTAN TAMBARANA KECAMATAN POSO PESISIR UTARA KABUPATEN POSO SULAWESI TENGAH - Rukmi, Rukmi (Universitas Tadulako, 2014)
Ebony is a kind of luxury wood belonging to the class I and class strong durable I. shiny black wooden porch and smooth with a distinctive pattern of brown interspersed combination of the red line, it is suitable for engraving materials, luxurious furniture that has a high decorative value. The study aims to determine the species composition of vegetation and conditions of the type of ebony (Diospyros celebica Bakh.) On Tambarana ebony forests. The usefulness of this research can be used as guidelines in the management of type of ebony.Â Research conducted in the forest group Tambarana around Fort Tambarana mountain at an altitude of 100-300 m above sea level in July and August 2013. The study used methods terraced path that consists of six lines of research. Each path along the 200m made measuring 20x20m plots of 10 plots. Sample plots, seedlings, saplings and poles placed nested sampling.Â It can be concluded that the group Tambarana ebony forests, relatively poor when compared to the type of dipterocarp forests in Kalimantan. The number of species to the level found 68 types of trees, 73 species of small trees, saplings and seedlings 71 species of 62 species; The types that dominate at all levels of the growth is Pometia pinnata FORB., Homalium foetidum Benth., Canarium littorale BL., Callophylum inophyllum L., Diospyros celebica Bakh., Palaquium quercifolium Burck .; Type ebony large diameter is more scarce. Keywords: species composition, ebony forest